Elective induction versus spontaneous labour in Latin America - Gláucia Virgínia Guerra; José Guilherme Cecatti; João Paulo Souza; Aníbal Faúndes; Sirlei Siani Morais; Ahmet Metin Gülmezoglu; Renato Passini Jr; Mary Angela Parpinelli; Guillermo Carroli (The World Health Organization, 2011)
OBJECTIVE: To assess the frequency of elective induction of labour and its determinants in selected Latin America countries; quantify success in attaining vaginal delivery, and compare rates of caesarean and adverse maternal and perinatal outcomes after elective induction versus spontaneous labour in low-risk pregnancies. METHODS: Of 37 444 deliveries in women with low-risk pregnancies, 1847 (4.9%) were electively induced. The factors associated with adverse maternal and perinatal outcomes among cases of spontaneous and induced onset of labour were compared. Odds ratios for factors potentially associated with adverse outcomes were calculated, as were the relative risks of having an adverse maternal or perinatal outcome (both with their 95% confidence intervals). Adjustment using multiple logistic regression models followed these analyses. FINDINGS: Of 11 077 cases of induced labour, 1847 (16.7%) were elective. Elective inductions occurred in 4.9% of women with low-risk pregnancies (37 444). Oxytocin was the most common method used (83% of cases), either alone or combined with another. Of induced deliveries, 88.2% were vaginal.The most common maternal adverse events were: (i) a higher postpartum need for uterotonic drugs, (ii) a nearly threefold risk of admission to the intensive care unit; (iii) a fivefold risk of postpartum hysterectomy, and (iv) an increased need for anaesthesia/analgesia. Perinatal outcomes were satisfactory except for a 22% higher risk of delayed breastfeeding (i.e. initiation between 1 hour and 7 days postpartum). CONCLUSION: Caution is mandatory when indicating elective labour induction because the increased risk of maternal and perinatal adverse outcomes is not outweighed by clear benefits.